PERPUSTAKAAN KHUSUS ANAK DI KABUPATEN KUBU RAYA, PROVINSI KALIMANTAN BARAT - Pratiwi, Dhea; Purnomo, Yudi; Affrilyno, Affrilyno (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2025)
The low literacy culture and interest in reading in Kubu Raya Regency can be overcome by bringing literacy culture and interest in reading closer to children from an early age. In addition, currently in Kubu Raya Regency there is no facility that can accommodate children's reading and learning activities according to their character and needs. Therefore, it is necessary to design a Children's Special Library in Kubu Raya Regency with the aim of providing a place for children in Kubu Raya Regency to read, learn, and carry out other activities that can support the learning process of children as the function of the library in general. The method used is the R. Wintaker eight-step design process method, which is very suitable for use in this design. This method will start from the initial stage which consists of the process of object recognition and definition, then proceed with the process of preparation, analysis, synthesis, evaluation and finally re-evaluation, so as to get a design concept in the form of a game of building facade shapes, colors, provision of natural environments in the form of parks, as well as the concept of space arrangement with an open system.